GW24-e2290 Effects of oxidatively modified low density lipoprotein on proliferation and osteodifferentiation of mesenchymal stem cells that co-cultured with vascular smooth muscle cells. (1st October 2013) - Xiaochun, Chen; Feng, Ding; Zhiping, Ge; Yongdong, Li; Yunzeng, Zou; Junbo, Ge
Abstract : Objectives: Increasing evidences shown the important role of bone marrow-derived mesenchymal stem cells (BM-MSCs) in wound healing and vascular remodelling in vivo . However, their mechanism in the development of atherosclerosis and vessel calcify remain unclear. Objective To investigate the effects of Oxidatively Modified Low Density Lipoprotein (ox-LDL ) on proliferation and osteodiferenliation of BM-MSCs that Co-cultured with Smooth Muscle Cells with or without osteogenic inductor being then we try to explain the mechanism of how MSCs participate in atherosclerosis. Methods: BM-MSCs and VSMCs were prepared from SD rats and co-cultured in a Transwell system, which allowed the diffusion of secreted factors but prevented cell contact between the two cell types. Four groups were designed according as factorial design, which were Combine group (both osteogenic inductor and ox-LDL), ox-LDL group, Osteogenic inductor group and control group. The proliferation of BM-MSCs was determined by MTT assay. The their effects on the osteogenic potential of BM-MSCs by cell morphology, real-time PCR, immunofluorescent staining, alkaline phosphatase (AKP) activity and Osteopontin (OPN) synthesis. Results: 1. The growth curve showed that cells number of all four groups increased along with time. The ability of promoting cellular proliferation in ox-LDL (5 mg/L) group were showed strongest in four groups, but that of combine group were opposite at 7days, 10 days and 14 days. 2. At the cultured 7 days, 10 days, all groups express OPN mRNA and AKP and but the combine group was highest. There was interaction between the two factors ( P < 0.01). 3. The result of Immunity histochemistry showed that the rate of OPN and AKP positive cells in combine group were the highest at 14 days. Conclusions: Increasing evidences indicated a link between bone marrow cells and the pathogenesis of atherosclerosis. It was recognized that a higher percentage of circulating endothelial progenitor cells expressed osteocalcin in patients with coronary atherosclerosis. Widespread increased myeloid calcifying cells contribute to ectopic vascular calcification in type 2 diabetes. Furthermore, mouse model and human studies have suggested that bone marrow-derived progenitor cells may contribute to a variety of vascular pathologies including calcification, atherosclerosis and intimal hyperplasia. In view of the capacity of differentiation into osteoblast from BM-MSCs, we investigated whether BM-MSCs was involved in the process of angiosteosis in atherosclerosis when exposed to vascular injure and hyperlipemia. Thus, we mimicked the phenotype transformation of VSMC exposed to hyperlipemia to investigate the differentiation of BM-MSCs. Data reported in this study demonstrated that ox-LDL significantly promoted proliferation of BM-MSCs co-cultured with VSMC, but not osteoblast differentiation. The proproliferative role of ox-LDL was neutralised by Osteogenic inductor, but apoptosis was induced instead. We results showed that ox-LDL can promote the proliferation of BM-MSCs, and Osteogenic Inductor mediated Osteodifferentiation marker expression in BM-MSCs in vitro .